Risk identification and assessment in production of meat product packaging - Yu. A. Kuzlyakina; V. S. Zamula; M. V. Kochneva (Теория и практика переработки мяса)
Production of convenient and inexpensive packaging materials is increasing due to the constant growth of consumer demand for safer food products. The paper examines the questions dedicated to the development and introduction of the safety and quality management system in enterprises producing packaging for the meat industry. The authors analyze the elements of safety and quality management for polypropylene packaging in a form of a tray, which is a final element of the united chain in production of whole-piece meat semi-finished products. The investigations were carried out in the operating enterprise in the Moscow region. Hazardous factors in production of polypropylene packaging were identified, risk analysis with assessment of the probability of emergence and realization of hazardous factors was carried out, a Pareto chart was built, unacceptable risks were determined, critical control points (CCP) were revealed, preventive and corrective measures were developed with account for the established critical limits and requirements for CCP monitoring were formulated. All stages of production process were subjected to risk analysis; the severity of consequences from hazardous factor realization and the probability of such realization were assessed by experts for each of these stages. It was established that “injection molding and chilling in a press-mold” is a CCT as there is a risk of increasing the maximum allowable concentrations of chemical substances and compounds (formaldehyde, ethyl acetate, alcohols and others) as a chemical factor with the severity of consequences of 3 and the probability of realization of 3. Using the Pareto chart, causes that had the highest effects on safety and quality of polypropylene packaging were grouped. It was established that nonobservance of preventive maintenance schedule for equipment and, as a consequence, possible equipment failure (80%) influenced to the higher degree the realization of chemical hazardous factor.